PERAGAAN BUSANA VIRTUAL SEBAGAI SARANA PROMOSI DI OBEDA BOUTIQUE SALATIGA - Setiyo Adi Nugroho; Andik Prakasa Hadi; Agus Priyadi; Eni Kristina Pujiastuti (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2023)
This research is about designing a virtual fashion show video for promotion at Obeda Boutique Salatiga. This research is purposed to display fashion products in fashion shows in the form of 3-dimensional animation, and to hold fashion shows through social media. The preparation of this promotional video utilizes the Multimedia Development Life Cycle (MDLC) research approach which follows six steps, namely (1) concept, for setting goals, target audience, and others. (2) design, to develop detailed specifications regarding style, appearance, and material requirements for animation production. (3) collection of materials, collect materials according to the needs of the project. (4) assembly, making all objects or animated materials. (5) testing, testing performance to ensure compliance with the expected specifications, and (6) distribution, producing the final product in video format with *.mp4 format. Based on the research results, the design of a virtual fashion show video as a means of promotion at Obeda Boutique Salatiga is appropriate to be published on all Obeda Boutique Salatiga social media. Keywords: (1) Promotional Video, (2) Virtual Video, (3) Promotional Media.